Translation, cultural adaptation and psychometric testing of short form quality of trauma patient experience measure (SF-QTAC-PREM) to a Swedish context - Elizabeth Mårtenson; Anna Kullberg; Anders Enocson; Katarina E Göransson (PLoS ONE, 2026)
Patients admitted to hospital due to trauma present with a multifaceted constellation of injuries, severity of injuries and comorbidities that require a complex and specialised somatic and psychological care system. Good care processes have been linked to better recovery and improved long-term health and health-related quality of life. There is both a knowledge gap around quality and safety of patient’s care following injury, as well as a lack of a validated questionnaire to systematically collect trauma patients’ experiences. The aim of this study was to translate, culturally adapt and determine the psychometric properties of the SF-QTAC-PREM acute care for use in a Swedish population of trauma patients. A prospective, cross-sectional study was performed in which patients at a Level 1 trauma centre in Sweden participated. Translation and adaptation was performed in accordance with the ISPOR and WHO guidelines, which generated a 22-item questionnaire. Thirty patients completed the test-retest, and a further 150 patients the psychometric testing. Reliability was established using Intraclass Correlation Coefficient (ICC), and weighted Cohen’s Kappa coefficient, which showed a moderate to substantial agreement, and good reliability. The psychometric properties of the questionnaire using Exploratory Factor Analysis identified a two-factor solution with two stand-alone items. A good internal consistency was shown between factors using Cronbach’s alpha (0.85 Information and care, 0.84 Patient safety), concluding that the factors were not able to be combined. Spearman’s R correlation showed weak (0.31) and moderate (0.58) positive relationships between the items and global rating scale contributing to a good overall construct validity. The new Swedish SF-QTAC-PREM acute care exhibited above acceptable external reliability, good overall internal consistency and construct validity.